Cover Picture: Opposite Face Sensitivity of CeO2 in Hydrogenation and Oxidation Catalysis (Angew. Chem. Int. Ed. 45/2014). Issue 45 (21st August 2014) - Vilé, Gianvito; Colussi, Sara; Krumeich, Frank; Trovarelli, Alessandro; Pérez‐Ramírez, Javier
<x xml:space="preserve">Abstract</x> Structure–performance relationships of ceria in heterogeneous reactions are revealed by J. Pérez‐Ramírez, A. Trovarelli, et al. in their Communication on page 12069 ff. The (111) surface prevalent in conventional polyhedral CeO2 particles outperforms in hydrogenation, while the (100) surface that is exposed in nanocubes dominates in oxidation. Artwork: Amalia Gallardo (ArteLi) and Marcel Reich.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>